Characterization of UV and chlorine contributions to transformation of 2, 3, 4-trihydroxybenzophenone under combined UV-chlorine treatment. (January 2021) - Zhang, Xinyi; Wei, Dongbin; Yu, Qi; Du, Yuguo
Abstract: Combined UV-chlorine treatment is a promising disinfection technology providing synergistic effects on bacteria-killing. The interaction between UV and chlorine would affect pollutants removal and disinfection by-products formation, while little is known about how UV and chlorine respectively contribute to pollutants transformation under combined UV-chlorine treatment. In this study, UV filter 2, 3, 4-trihydroxybenzophenone (2, 3, 4-THBP) was selected as a model compound to investigate the transformation characteristics and acute toxicity variation under combined UV-chlorine treatment. Especially, separative UV and chlorination treatments were conducted to illustrate their respective contribution in combined UV-chlorine treatment. It was found that the optimal removal percentage of 2, 3, 4-THBP under combined UV-chlorine treatment was 85.3% within 5 min and kept stable until 3 h at 3-equivalent (equiv.) of free available chlorine (FAC) and 1 mW/cm 2 of irradiation intensity. Correspondingly, acute toxicity of reaction mixture at 3 h increased twice as high as that of 2, 3, 4-THBP itself. Four transformation products were tentatively identified, and their formation possibly involved the reactions of chlorine substitution, oxidation, hydroxylation, and hydrolysis. FAC initiated the preliminary transformation of 2, 3, 4-THBP, and the synergistic effects of UV and chlorine promoted the further transformation of intermediates from chlorination treatment. Most important was that, 2, 3, 4-THBP could form some toxic products in the real ambient water matrix under solar irradiation, and acute toxicity of reaction mixture was 1.84 times higher than that of 2, 3, 4-THBP. This study would provide a better understanding on the transformation characteristics of pollutants under combined UV-chlorine treatment, and provide a reference for optimizing disinfection treatment. Graphical abstract: Image 1 Highlights: 2, 3, 4-THBP can be degraded during UV-chlorine combination disinfection. Chlorine is responsible for preliminary transformation of 2, 3, 4-THBP. Synergistic effects of UV and chlorine promote intermediates transformation. Acute toxicity of 2, 3, 4-THBP solution treated by UV-chlorine significantly increases.